2023
DOI: 10.3390/polym15122712
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Potential of Fique Fiber as a Natural Composite Material: A Comprehensive Characterization Study

Abstract: Many studies available in the literature focus mainly on the mechanical characterization of fiber, leaving out other physicochemical and thermogravimetric analyses that allow for establishing its potential as an engineering material. This study characterizes fique fiber for its potential use as an engineering material. The fiber’s chemical composition and physical, thermal, mechanical, and textile properties were analyzed. The fiber has a high holocellulose content and low lignin and pectin content, indicating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 83 publications
0
4
0
Order By: Relevance
“…The average linear density was found to be 58.85 tex (i.e., 1000 m of CS fibre had a mass of 58.85 g), and the standard deviation was 35.8%. The dispersion of linear density values obtained in this study was plotted in the histogram and found to be normally distributed [24]. The segments between 40 and 80 tex have the highest frequencies.…”
Section: Fibre Linear Densitymentioning
confidence: 70%
See 3 more Smart Citations
“…The average linear density was found to be 58.85 tex (i.e., 1000 m of CS fibre had a mass of 58.85 g), and the standard deviation was 35.8%. The dispersion of linear density values obtained in this study was plotted in the histogram and found to be normally distributed [24]. The segments between 40 and 80 tex have the highest frequencies.…”
Section: Fibre Linear Densitymentioning
confidence: 70%
“…The extracted CS fibres were equilibrated under standard test conditions, i.e., 20 °C temperature and 65% RH for 24 h [24]. The physical characterization of the CS fibre was developed by determining the length, diameter, linear density, and density of fibres.…”
Section: Physical Characterization Of Coconut Spathe Fibrementioning
confidence: 99%
See 2 more Smart Citations